Efgartigimod therapy for immune checkpoint inhibitor–associated myasthenia gravis with myositis: a case report - Feiteng Qi; Qi Sun; Haifeng Wang; Yong Zhang (BMC Neurology)
Abstract The advent of immune checkpoint inhibitors (ICIs) has transformed cancer therapy, but their association with immune-related adverse events presents a new and complex challenge for clinicians. In this report, we present the case of a 60-year-old Han Chinese woman who developed myasthenia gravis (MG) with myositis after pembrolizumab treatment for breast cancer. The patient presented with ptosis, slurred speech, limb weakness, and ocular fixation. Her creatine kinase level was elevated but she reported no muscle pain. The patient was diagnosed with ICI-associated MG with myositis. Before presenting to us, the patient had received low doses of intravenous methylprednisolone followed by oral prednisone, but her symptoms had continued to worsen. Her muscle strength improved significantly after we treated her with efgartigimod. This report is the first description of efgartigimod use in the treatment of ICI-associated MG with myositis, a new strategy for the treatment of this disease.